Structural and optical properties of Zinc selenide nanocrystal and quantum dots colloidal prepared via hydrothermal route - Ashari, Fakhrurrazi (2017)
Zinc Selenide which show a potential application in electronic devices such as photovoltaic devices, light emitting devices and photodetector has been synthesized through a hydrothermal method. It has been found that the hydrothermal reaction conducted at 180 °C for 32 hours is optimum to produce NCr ZnSe, while the hydrothermal reaction at 150 °C for 8 hours is optimum for ZnSe QDs. Formation of ZnSe in nanocrystal (NCr) and quantum dots (QDs) using different source and different concentration ratio has been study in detail to optimize the production condition. The concentration effect of the precursor (ZnCl2/ Zn(O2CCH3)2(H2O)2) which varied from 0.25:1, 0.5:1, 1:1, 2:1, 3:1 until 4:1 has been explained in terms of its structured, morphology, composition and the optical behavior. The structural, morphology, compositional and optical properties of the nanocrystal and quantum dots were study using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM), X-ray Fluorescence (XRF), UV-Vis NIR Spectroscopy (UV-Vis) and Photoluminescence (PL). The difference of NCr and QDs of ZnSe has been explored in detail through their structural properties, particle size, absorption and optical band gap (Eg) also emission peak. For NCr, the particle size is around 0.08 μm to 15.7 μm for both precursor (ZnCl2/ Zn(O2CCH3)2(H2O)2). The system structure is cubic structure (ZnCl2) and sphere structure (Zn(O2CCH3)2(H2O)2). While for QDs, the particle size is around 6.2 nm to 49.1 nm (ZnCl2/ Zn(O2CCH3)2(H2O)2) and the structure system is cubic and sphere structure. All this will affect and show the difference of optical behavior between NCr and QDs and it is related to the quantum confinement effect especially for the QDs samples. The absorption peak is at 460 nm, while the Egvalue at 2.60 eV and emission peak is at 486 nm (blue region). The result is for NCr while for QDs, the absorption peak around 313 nm to 317 nm with Eg value is around 3.60 eV to 3.80 eV with emission peak at range 450 nm to 490 nm. The optical behavior will show the difference between NCr and QDs sample, when the size is smaller the color emitted light will shift from red to blue shift while the optical band gap (Eg) will increase. So, it has found that the optical behavior is strongly affected by the morphological behavior of the nanocrystal and quantum dots